Social Criticism in Heinrich Heine’s Poem ‘Die Heimkehr’ - Riswansyah Riswansyah; Syamsu Rijal; Laelah Azizah (Universitas Negeri Makassar, 2026)
Abstract. This study employs a qualitative-descriptive method through textual analysis of the poem Die Heimkehr. The analysis is conducted by examining elements of the poem’s physical structure (diction, imagery, figurative language, typography, and rhyme) as well as its inner structure (theme, emotion, atmosphere, tone, and message), which are then related to the social and historical context of nineteenth-century Germany. The data are derived from the text of Die Heimkehr and supporting literature on the socio-political conditions of Germany during Heine’s era. The results of the study indicate that Die Heimkehr contains social criticism encompassing eight main aspects: politics, economy, education, morality, religion, culture, family, and gender. Heine conveys this criticism through irony, satire, symbolism, and poetic imagery that conceal social messages behind linguistic beauty. The poem’s physical structure is employed to construct subtle irony that remains safe from censorship, while its inner structure reveals the collective anxiety of German society under political repression, poverty, social inequality, and moral declineKeyword: The Heimkehr, Social Criticism, Sociology of Literature, Poetry